Communication—Defect-Free Filling of High Aspect Ratio Through Vias in Ultrathin Glass. Issue 1 (27th November 2018) - Chang, Yiu-Hsiang; Tseng, Pei-Lien; Lin, Jen-Chieh; Chen, Jie-Chi; Huang, Meng-Chi; Lin, Hung-Yi; Pollard, Scott; Mazumder, Prantik
Abstract : We report an all-solution, simple process (DC plating with single additive) for metallizing high aspect ratio (AR = 5 and AR∼12) through vias in ultrathin glass (thickness ∼100 um). Highly uniform and continuous Cu seed layer is first achieved by a simple surface modification, Sn/Pd catalyst adsorption and Cu electroless plating. Subsequently, the vias are filled by DC plating in the presence of a single additive nitrotetrazolium blue chloride (NBT). The strong inhibition effect of NBT is exploited to first bridge the center of the vias followed by filling of two blind vias.